Prognostic role of Wnt and Fzd gene families in acute myeloid leukaemia. Issue 3 (8th January 2021) - Dai, Yifeng; Cheng, Zhiheng; Fricke, Doerte R.; Zhao, Hongyou; Huang, Wenhui; Zhong, Qingfu; Zhu, Pei; Zhang, Wenjuan; Wu, Zhihua; Lin, Qing; Zhu, Huoyan; Liu, Yan; et al.
Abstract: Wnt‐Fzd signalling pathway plays a critical role in acute myeloid leukaemia (AML) progression and oncogenicity. There is no study to investigate the prognostic value of Wnt and Fzd gene families in AML. Our study screened 84 AML patients receiving chemotherapy only and 71 also undergoing allogeneic haematopoietic stem cell transplantation (allo‐HSCT) from the Cancer Genome Atlas (TCGA) database. We found that some Wnt and Fzd genes had significant positive correlations. The expression levels of Fzd gene family were independent of survival in AML patients. In the chemotherapy group, AML patients with high Wnt2B or Wnt11 expression had significantly shorter event‐free survival (EFS) and overall survival (OS); high Wnt10A expressers had significantly longer OS than the low expressers (all P  < .05), whereas, in the allo‐HSCT group, the expression levels of Wnt gene family were independent of survival. We further found that high expression of Wnt10A and Wnt11 had independent prognostic value, and the patients with high Wnt10A and low Wnt11 expression had the longest EFS and OS in the chemotherapy group. Pathway enrichment analysis showed that genes related to Wnt10A, Wnt11 and Wnt 2B were mainly enriched in 'cell morphogenesis involved in differentiation', 'haematopoietic cell lineage', 'platelet activation, signalling and aggregation' and 'mitochondrial RNA metabolic process' signalling pathways. Our results indicate that high Wnt2B and Wnt11 expression predict poor prognosis, and high Wnt10A expression predicts favourable prognosis in AML, but their prognostic effects could be neutralized by allo‐HSCT. Combined Wnt10A and Wnt11 may be a novel prognostic marker in AML.